Komunikasi Pemasaran Pengrajin Bambu Kreatif di Tasikmalaya - Santi Susanti; Rachmaniar Rachmaniar; Iwan Koswara (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Tasikmalaya known as the centers of bamboo handicraft industry in West Java. It produces various products, from daily household equipment in the form of rough woven with low prices to creative bamboo products with high prices for the upper middle market. Products are distributed for domestic needs and demand of foreign buyers. This study reveals the marketing communication behavior of creative bamboo entrepreneurs in Tasikmalaya in developing a creative bamboo craft business. A qualitative method with a case study approach was used to obtain information about the behavior of bamboo handicraft entrepreneurs in Tasikmalaya in marketing their products. Data were collected through in-depth interviews with creative bamboo entrepreneurs who still actively running their businesses and willing to provide information about the businesses they are running. Data were also collected through non-participatory observations at the location and conducted a literature review and documents related to the research. Data analysis, data checking and validity of the data were conducted through Miles and Huberman's interactive data analysis concept. The results showed that the communication behavior conducted by creative bamboo entrepreneurs consisted of internal communication behavior and external communication behavior. Internal communication behavior is conducted on workers with the principle of kinship. Humanist approach is used to maintain production stability.The form of external communication behavior is tailored to whom they're being faced. Face-to-face communication and mediated communication are used in marketing bamboo handicraft products.